PATTERN OF DISTRIBUTION OF ANTHOCYANIN PIGMENTS IN THE DIFFERENT TAXA OF LANTANASPECIES (VERBENACEAE) - SHEEJA.M.S,; A.K.BOPAIAH, (International Journal of Pharma and Bio Sciences, 2016)
Lantana species are widespread around the world and they are plants ound as ornamental as well as wild varieties. The colors of the flowers vary largely and the variation in colour is due to the presence of Anthocyanins. Anthocyanins are pigments that are responsible for the coloring of the plant parts; they are localized in various parts of the plants and are known to impart brilliant colors.Anthocyanins are known to occur in different colors based on the pH and thereby anthocyanins are used as pH indicators. Study of anthocyanins in varying pH can be done using spectrophotometric methods. This study involves extraction of anthocyanin pigments of Lantana flowers at different pH ranges by pH differential method (pH1 and pH5) and estimation of the anthocyanin content at 520nm, the result is an estimate of the total monomeric content of anthocyanins. Anthocyanin pigments are also estimated at two different wavelengths at 530nm and 657nm and the relative anthocyanin content expressed. The study clearly indicated the varying anthocyanin content with the change in colour of the flowers. This change in the chemical nature of the anthocyanin pigments may be due to genetic variation shown by the plants and thereby, leading to differing anthocyanins in the plant.